The Winning trainer : winning ways to involve people in learning - Eitington, Julius E. (Texas : Gulf Professional Pub., 1996)
This volume contains advice for corporate trainers who want to involve their students actively in the learning experience. It contains the following features: more than 100 pages of handouts and worksheets, ready to be copied and distributed; and numerous examples, model dialogues and answers.
1. How to Start Things Off -- 2. Using Small Groups Effectively -- 3. Basic Techniques for Small Group Training -- 4. Additional Techniques for Small Group Training -- 5. Role Playing -- 6. Using Games and Simulations -- 7. Using Exercises -- 8. Using Puzzles -- 9. Instrumentation -- A Tool for Self-Discovery Learning -- 10. Defining a Problem and Generating Data About It -- 11. Generating Solutions to a Problem -- 12. Selecting and Implementing a Solution -- 13. Team Building: Overcoming the "Lone Ranger" Syndrome -- 14. The In-Basket Exercise -- How to Conduct and Design It -- 15. Other Key Group-in-Action Tools -- 16. Involving Participants in Film/Video 00 17. Maximizing Participation and Learning in the Case Method -- 18. "If You Must Lecture ..." -- 19. Using Participative Methods to Evaluate Training -- 20. How to Overcome the Transfer Problem -- 21. Ancillary Issues and Techniques
Includes index.
Keywords: STAFF -- TRAINING